Evaluation of physical fitness in water polo players according to playing level and positional role - Botonis, P. G.; Toubekis, A. G.; Platanou, T. I. (Sports, 2018)
Background: We aimed to investigate whether water polo players of different playing levels and positions differ in fitness parameters (i.e., strength, aerobic endurance, and anaerobic potential). Methods: Twenty-four water polo players were assigned to international- (IL) and national-level (NL) groups or to centers and peripherals. At the beginning of preseason training, maximal bench press strength was measured and a speed-lactate test (5 × 200m) was performed to determine the speed corresponding to lactate concentrations of 4.0 (V4), 5.0 (V5), and 10.0 (V10) mmol·L-1. Results: Maximal muscular strength was similar between international- and national-level water polo players, but it was higher in centers than in peripherals (109.2 ± 12.2 kg vs. 96.9 ± 8.5 kg, p = 0.007). IL players showed higher V4, V5, and V10 compared to NL players (V4, IL: 1.27 ± 0.04 m·s-1 vs. NL: 1.17 ± 0.06 m·s-1), (V5, IL: 1.33 ± 0.03 m·s-1 vs. NL: 1.22 ± 0.05 m·s-1), and V10 (IL: 1.50 ± 0.31 vs. NL: 1.35 ± 0.06 m·s-1) (p < 0.01)). However, no significant differences were detected between centers and peripherals inV4, V5, and V10. Conclusions: We suggest that V4, V5, and V10 distinguish playing level in water polo, whereas they are comparable between playing positions. Although maximal strength is similar between playing levels, it is different between playing positions